Predation attempt by a long-tailed weasel Neogale frenata on a Holcosus gaigeae lizard - Nahuat-Cervera, Pedro E.; Arellano-Ciau, J. Ismael (Therya Notes, 2023)
The long-tailed weasel, Neogale frenata, is a small mammal occurring from southern Canadá to northern South America, whose diet consists mainly of small mammals, and occasional consumption of reptiles. We herein describe the attempted predation by a N. frenata on a Holcosus gaigeae lizard. Our observation was made during an ad libitum bird watching in the municipality of Felipe Carrillo Puerto, Quintana Roo, México. Two events were recorded in which the weasel was observed approaching the lizard, trying to position itself for an approach from behind and actively chasing it around. This predation behavior coincides with previously reported hunting strategies for N. frenata for medium-sized prey and represents the first record of interaction between these 2 species.